Mozarts "La clemenza di Tito" und der deutsche Nationalgedanke: Ein Beitrag zur "Titus"-Rezeption im 19. Jahrhundert - Durante, Sergio (Die Musikforschung, 2000)
The fortune of Mozart's <La clemenza di Tito> in the German speaking space is examined through diverse evidence: the correspondence Goethe-Schiller and its references to the critical positions of Friedrich Reichardt in the Journal "Deutschland", the early identification of Mozart's figure as German national musician; the production circumstances of the first production in German by the Joseph Sekonda truppe and the later fortune are related to the political situation in Germany during the Napoleon era and to the political understanding of the subject in the elaboration of the libretto by Friedrich Rochlitz. The relevance of the opera for German composers like Carl Maria von Weber and Heinrich Marschner contextualized and an explanation of both its rise and fall is related to the changing notion of 'Romantic' between the very beginning and the second decade of the 19th Century.